Un raro caso di tenosinovite tubercolare in operatore sanitario a seguito di incidente occupazionale per puntura da ago cavo infetto. Aspetti di prevenzione e valutazione medico legale / A rare case of tubercular tenosynovitis in hospital surgeon as a result of an occupational accident caused by puncture with an infected needle. Prevention aspects and legal-medical evaluation - delli Carri, R.; Piscozzi, P.; Massimelli et al., M. (La Medicina del Lavoro, 2010)
Trattasi di caso di Chirurgo ospedaliero, con incarico secondario di Preposto ex Art. 19 of D.lgs. 81/2008 per la Divisione di Chirurgia del Nosocomio dove presta servizio che, durante l’espletamento di una procedura di routine in ambulatorio chirurgico finalizzata all’aspirazione di una raccolta lombare destra in un paziente sospettato di essere affetto da TBC, accidentalmente si pungeva il V dito della mano sinistra con l’ago utilizzato per tale procedura. Si determinava un interessamento del V dito della mano sinistra limitatamente ai soli tessuti molli preservando l’articolazione e l’osso ed un coinvolgimento tenosinoviale di tutta l’estremità. Ciò ha determinato ripercussioni in ambito assicurativo con una astensione dal lavoro per 126 gg. e una valutazione di danno biologico per INAIL pari al 2%. A rare case of tubercular tenosynovitis in hospital surgeon as a result of an occupational accident caused by puncture with an infected needle. Prevention aspects and legal-medical evaluation Background: The subject was a hospital surgeon who, in the course of routine outpatient surgery with aspiration to collect right lumbar material in a patient with suspected TB infection, accidentally punctured the fifth finger of the left hand with the needle used for this procedure. This led to involvement of the fifth finger of the left hand restricted to the soft tissue with preservation of joint and bone and tenosynovial involvement of the entire extremity. Objectives: To draw attention to the repercussions for insurance with resulting absence from work for 126 days and an assessment of biological impairment of 2% by the Insurance Institute (INAIL). Methods: A case report is described of rare occupational tubercular synovitis. Conclusions: A rare event is reported that occurred in a senior staff member with particular insurance repercussions.